The War Against Corruption in Nigeria: The Problems with the Solution - Berebon, Charles B (dialektika kontemporer, 2024)
Corruption remains one of the most debated and concerning issues in Nigeria, receiving widespread attention from individuals, organizations, and government bodies. This persistent challenge has deeply embedded itself in the political system, leading to detrimental effects across various sectors of society. Over the years, successive Nigerian administrations have implemented various measures to combat corruption, recognizing its negative impact on the nation’s political and economic stability. However, despite these efforts, the results have often been underwhelming, with corruption continuing to thrive at alarming rates. This paper explores the concept of corruption, examines the various anti-corruption strategies employed by different Nigerian regimes, and critiques the reasons for their limited success. Ultimately, the paper argues that while administrative capacity is vital in the fight against corruption, political will is the most critical factor for success.